Ultrathin copper foil for laser processing and preparation method thereof

By roughening the sides of the copper foil and electroplating the metal alloy layer, the laser absorption capacity is improved, and the problem of additional browning in the prior art is solved, and the effect of simplifying the production process and reducing costs is achieved.

CN119676975APending Publication Date: 2025-03-21JIUJIANG TELFORD ELECTRONICS MATERIAL CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411576745.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-06
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

In the prior art, when laser formation of microblind holes in printed circuit boards, it is necessary to add a browning process or introduce an unconventional anti-rust layer metal component, resulting in high production costs and complex processes.

Method used

By roughening the side and non-pressure sides of the pressed insulating layer of the copper foil, and electroplating the metal alloy layer on the non-pressure side and coating the silane, the laser absorption capacity of the copper foil is improved, avoiding additional browning.

Benefits of technology

It is achieved without increasing the browning process, improving the laser absorption capacity of copper foil, simplifying the production process, reducing costs, and reducing the impact on the etching liquid.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119676975A_ABST
    Figure CN119676975A_ABST
Patent Text Reader

Abstract

The invention relates to an ultrathin copper foil for laser processing and a preparation method of the ultrathin copper foil, roughening treatment is carried out on a press-fit insulating layer side surface and a non-press-fit side surface of the copper foil, a metal alloy layer is electroplated on the press-fit insulating layer side surface, silane is coated on the press-fit insulating layer side surface, and a metal alloy layer is electroplated on the non-press-fit side surface. According to the method, a browning process does not need to be specially added in a printed circuit board process, or an unconventional antirust layer metal component does not need to be introduced, so that the production cost is saved, the production process is shortened, the surface metal is relatively thin, the subsequent removal is simple, and the influence on an etching solution is relatively small.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of electrolytic copper foil processing, and particularly relates to an ultra-thin copper foil for laser processing and a preparation method thereof. Background Art

[0002] In recent years, the printed circuit board industry has adopted laser drilling as a solution for interlayer interconnection of printed circuit boards to increase the interconnection density of circuits, making the design of printed circuit boards more compact and improving the integration and performance of printed circuit boards. With the miniaturization of the design patterns of printed circuit boards, laser drilling has adopted micro blind holes with apertures below 100μm to achieve interlayer connections, and even blind hole connection technology below 75μm has been developed. At present, this type of micro blind hole is mostly formed by carbon dioxide laser and UV laser processing. Among them, carbon dioxide laser has high hole-forming energy, high hole-forming efficiency and good consistency, and is widely used in the preparation of micro blind holes above 50μm.

[0003] There are two ways to form micro-blind holes using CO2 laser: laser direct drilling (LDD) and etching copper foil first to open the window (CFM) and then drilling. The process of laser direct drilling (LDD) is simple, that is, the CO2 laser directly ablates the copper foil and the insulating resin layer under the copper foil to form micro-blind holes.

[0004] Since the copper foil surface has a very low absorption rate for CO2 laser, in order to increase the copper foil's absorption of CO2 laser energy, the printed circuit board factory generally needs to pre-brown or blacken the copper foil surface to increase its surface roughness, increase the specific surface area, and improve the absorption rate of laser energy. The laser direct drilling process (LDD) in the printed circuit board factory usually requires a copper thickness of less than 8μm. The commonly used copper foil thickness specifications in the printed circuit board factory are 3μm, 5μm, 9μm, 12μm and 18μm. Among them, the 12μm copper foil and the 18μm copper foil need to be subjected to copper reduction treatment after the copper foil is pressed to reduce the surface copper thickness, and then the copper foil surface is subjected to browning treatment, which increases the processing flow and cost.

[0005] Patent CN104160792 B discloses a copper foil with an alloy layer composed mainly of Sn and Cu on the surface. The reason is that under the same conditions, the laser absorption rate of Sn is more than twice that of Cu. Therefore, after the alloy layer is set on the surface of the copper foil, no pre-treatment such as browning is required. Micro blind holes of a specific diameter can be formed by directly irradiating the surface of the copper foil with a carbon dioxide laser. However, this ultra-thin copper foil needs to be attached with a carrier copper foil, and the price of the carrier copper foil is relatively high, which increases the cost of use for the printed circuit board factory. At the same time, the patent introduces that the laser absorption rate of Sn at the same room temperature and the same surface roughness is more than 2 times higher than that of Cu, and the laser absorption capacity of Sn relative to Cu is not significantly improved; and the preferred thickness of the laser absorption layer is between 0.3μm and 3μm, and the thickness of the laser absorption layer is high relative to the thickness of the copper foil. Etching and removal takes a long time and is difficult, and a large amount of Sn metal is mixed in the etching solution, which has a great impact on the etching solution. Summary of the invention

[0006] The technical problem to be solved by the present invention is to provide an ultra-thin copper foil for laser processing and a preparation method thereof. The copper foil does not require a special browning process to be added during the printed circuit board process, or the introduction of unconventional anti-rust layer metal components, thereby saving production costs, shortening the production process, and having a relatively thin surface metal thickness, which is simple to remove subsequently and has relatively little impact on the etching solution.

[0007] The present invention provides an ultra-thin copper foil for laser processing, wherein a roughening treatment is performed on the laminated insulating layer side and the non-laminated side of the copper foil, and a metal alloy layer is electroplated on the laminated insulating layer side and silane is coated, and a metal alloy layer is electroplated on the non-laminated side.

[0008] Preferably, the copper foil has a thickness between 5 μm and 8 μm.

[0009] Preferably, the thickness of the copper teeth on both sides of the copper foil from valley to valley is greater than 4.5 μm.

[0010] Preferably, the tensile strength of the copper foil is greater than 450 MPa, more preferably greater than 500 MPa.

[0011] Preferably, the roughness Rz of the side of the laminated insulating layer is less than 2.5 μm, more preferably less than 2.0 μm; the roughness Rz of the non-laminated side is between 0.5 μm and 2.0 μm, more preferably between 0.6 μm and 1.2 μm.

[0012] Preferably, the metal alloy layer is a component of a copper foil anti-rust layer.

[0013] Preferably, the metal alloy in the metal alloy layer includes one or more of Ni, Mo, Zn, Cr, Co, and W.

[0014] Preferably, the thickness of the metal alloy layer is within 1 nm-300 nm.

[0015] Preferably, the copper teeth height of the non-pressed side surface is between 300nm and 800nm.

[0016] Preferably, the brightness L* value of the non-pressed side is less than 50, more preferably less than 30.

[0017] The schematic diagram of the copper foil of the present invention and the schematic diagram of the printed circuit board after the copper foil of the present invention is pressed together are as follows: Figure 3 shown.

[0018] The present invention also provides a method for preparing an ultra-thin copper foil for laser processing, comprising the following steps:

[0019] (1) preparing raw foil;

[0020] (2) passing the raw foil obtained in step (1) through a pickling tank to remove the oxide layer on the surface, and then roughening and curing the pressed insulating layer side and / or the non-pressed side of the raw foil;

[0021] (3) After the treatment in step (2), the surface of the raw foil is further electroplated with non-copper metal to form an alloy layer; silane is coated on the side of the laminated insulating layer and dried to obtain an ultra-thin copper foil for laser processing.

[0022] The above-mentioned processes of preparing raw foil, pickling, roughening, curing, non-copper metal plating (including blackening, ashing, passivation or one of them), silane coating, etc. can all be carried out under conventional copper foil production process conditions. The roughening treatment and curing treatment of the side of the laminated insulation layer and the non-laminated side can be carried out successively or simultaneously.

[0023] The present invention prepares an ultra-thin copper foil (thickness 5 μm-8 μm) that can be directly processed by laser; performs roughening treatment on the laminated insulation layer side and the non-laminated side of the ultra-thin copper foil; and uses a metal alloy layer on the non-laminated side to reduce the surface brightness; and achieves the purpose of direct carbon dioxide laser drilling by increasing the roughness of the non-laminated side and reducing the surface brightness. The specific structure is as follows Figure 2 and Figure 3 shown.

[0024] When the laser is irradiated on the non-pressed side of the copper foil, due to the increased surface roughness of the copper foil and the uneven surface of the copper foil, multiple reflections will inevitably occur. The material surface repeatedly absorbs the laser reflections, which improves the absorption capacity of infrared lasers. The metal alloy layer on the surface of the copper foil, such as Ni metal, can reduce the brightness of the surface and also improve the absorption rate of infrared lasers. The copper teeth height of this ultra-thin copper foil surface is between 300nm-800nm, and the copper teeth height is small. The surface roughness increases while the brightness decreases, which is conducive to increasing laser absorption.

[0025] Beneficial Effects

[0026] (1) The present invention solves the problem of adding a surface browning / blackening process to the copper foil and removing the surface browning / blackening process when the copper foil forms micro blind holes for interlayer conduction by laser in a printed circuit board factory due to the poor laser absorption of the copper foil, by increasing the roughness of the non-laminated side and reducing the brightness of the surface.

[0027] (2) The present invention realizes the processing of ultra-thin copper foil for 5-8 μm laser processing, avoids the use of carrier copper foil, and saves costs for printed circuit board factories. At the same time, the surface component is an anti-rust layer component, and there is no need to increase the laser absorption rate of Sn metal. The surface metal thickness is relatively thin, and subsequent removal is simple, and the impact on the etching solution is relatively small. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 The figure is a comparison diagram of the processing flow of the copper foil of the present invention and the processing flow of the prior art.

[0029] Figure 2 The figure is a comparison diagram between the copper foil of the present invention and the conventional copper foil.

[0030] Figure 3 Two side views of the copper foil of the present invention are shown. DETAILED DESCRIPTION

[0031] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.

[0032] Example 1

[0033] (1) Raw foil preparation: Raw foil is produced by electrolysis, and the process parameters are as follows:

[0034] Copper concentration: 90-100g / L;

[0035] Sulfuric acid concentration: 110-120g / L;

[0036] Chloride ion concentration: <30mg / L;

[0037] Glue concentration: <20mg / L;

[0038] Temperature: 50℃;

[0039] Current density: 70A / dm 2 .

[0040] (2) Pickling pretreatment: The electrolytic copper foil to be treated is passed through a pickling tank to remove the surface oxide layer. The process parameters are as follows:

[0041] Copper concentration: <10g / L;

[0042] Sulfuric acid concentration: 140±5g / L;

[0043] Temperature: 28℃;

[0044] Preprocessing time: 8S.

[0045] (3) Roughening treatment: The raw foil passes through the roughening treatment tank to promote the growth of copper nodules on the surface of the electrolytic raw foil, increase the contact area with the insulating layer and enhance the bonding strength. This step only roughens the side of the pressed insulating layer of the copper foil. The process parameters are as follows:

[0046] Copper concentration: 12 g / L;

[0047] Sulfuric acid concentration: 140g / L;

[0048] Temperature: 28℃;

[0049] Plating time: 7S;

[0050] Current density: 60A / dm 2 .

[0051] (4) Curing electroplating: The raw foil roughened in step C is cured to make the roughened copper nodules more firmly bonded to the raw foil substrate. In this step, only the side of the pressed insulating layer of the copper foil is cured. The process parameters are as follows:

[0052] Copper concentration: 50g / L;

[0053] Sulfuric acid concentration: 120g / L;

[0054] Temperature: 50℃;

[0055] Plating time: 7S;

[0056] Current density: 70A / dm 2 .

[0057] (5) Repeat steps (3) and (4) once or twice according to the roughness requirements to increase the number and size of copper nodules after treatment.

[0058] (6) Roughening treatment: The raw foil passes through the roughening treatment tank to promote the growth of copper nodules on the surface of the electrolytic raw foil, increase the specific surface area and laser absorption capacity. This step only roughens the non-pressed layer side of the copper foil. The process parameters are as follows:

[0059] Copper concentration: 12 g / L;

[0060] Sulfuric acid concentration: 140g / L;

[0061] Temperature: 28℃;

[0062] Plating time: 7S;

[0063] Current density: 60A / dm 2 .

[0064] (7) Curing electroplating: The raw foil roughened in step (6) is cured to make the roughened copper nodules more firmly bonded to the raw foil substrate. In this step, the non-pressed insulating layer side of the copper foil is cured. The process parameters are as follows:

[0065] Copper concentration: 50g / L;

[0066] Sulfuric acid concentration: 120g / L;

[0067] Temperature: 50℃;

[0068] Plating time: 7S;

[0069] Current density: 70A / dm 2 .

[0070] (8) Repeat steps (6) and (7) once or twice according to the roughness requirements to increase the number and size of copper nodules after treatment.

[0071] (9) Blackening treatment: A layer of Ni is deposited on both sides of the foil after rough curing to provide the copper foil with better chemical corrosion resistance and laser absorption ability. The process parameters are as follows:

[0072] K 4 P 2 O 7 =85g / L;

[0073] NiSO 4 .6H 2 O = 4.5 g / L;

[0074] Current density: 10A / dm 2 ;

[0075] Blackening liquid temperature: 40℃;

[0076] Blackening liquid pH = 8.5;

[0077] Electroplating time: 7S.

[0078] (10) Ashing treatment: The blackened foil is electroplated with potassium pyrophosphate and zinc sulfate complex solution system, and a layer of Zn is electroplated on both sides of the copper foil to provide high temperature anti-oxidation performance. The process parameters are as follows:

[0079] K 4 P 2 O 7 =85g / L;

[0080] ZnSO 4 .6H 2 O = 5.5 g / L;

[0081] Current density: 10A / dm 2 ;

[0082] Ashing liquid temperature: 40℃;

[0083] Ashing liquid pH = 8.5;

[0084] Electroplating time: 7S.

[0085] (11) Passivation treatment: When the original foil passes through the chromic anhydride solution system, a layer of Cr is electroplated on both sides of the copper foil to provide room temperature anti-oxidation performance. The process parameters are as follows:

[0086] Cr 6+ (chromic anhydride) = 1.5 g / L;

[0087] Current density: 15A / dm 2 ;

[0088] Passivation solution temperature: 35°C;

[0089] Passivation solution pH = 11;

[0090] Electroplating time: 7S.

[0091] (12) Silane coating: A layer of silane coupling agent is applied on the copper foil laminated insulation layer by roller coating and spraying to enhance the chemical bonding between the copper foil and the substrate. The process parameters are as follows:

[0092] The types of silanes are: epoxy silanes;

[0093] Si content>1200ppm;

[0094] The silane solution is clear and transparent.

[0095] (13) Drying: Drying the residual moisture on the foil surface and promoting the coupling reaction between the silane coupling agent and the hydroxyl groups on the surface of the copper foil to obtain an ultra-thin copper foil for laser processing.

[0096] The basic physical properties of the finished ultra-thin copper foil for laser processing are tested. The thickness of the copper foil is 6μm; the tensile strength of the copper foil is greater than 500MPa. The side of the copper foil laminated insulation layer has a roughening treatment, an anti-rust layer and silane, with a roughness of Rz2.0μm. The non-laminated side of the copper foil has a roughening treatment and an anti-rust layer, with a roughness of Rz0.9μm. The copper teeth height on the non-laminated side of the copper foil is 500nm. The non-laminated side surface is composed of various metals such as Ni, Zn, Cr, and Co. The non-laminated side surface of the copper foil contains a metal alloy layer, with a total of 50mg / m 2 .

[0097] Example 2

[0098] (1) Raw foil preparation: Raw foil is produced by electrolysis, and the process parameters are as follows:

[0099] Copper concentration: 90-100g / L;

[0100] Sulfuric acid concentration: 110-120g / L;

[0101] Chloride ion concentration: <30mg / L;

[0102] Glue concentration: <20mg / L;

[0103] Temperature: 50℃;

[0104] Current density: 70A / dm 2 .

[0105] (2) Pickling pretreatment: The electrolytic copper foil to be treated is passed through a pickling tank to remove the surface oxide layer. The process parameters are as follows:

[0106] Copper concentration: <10g / L;

[0107] Sulfuric acid concentration: 140±5g / L;

[0108] Temperature: 28℃;

[0109] Preprocessing time: 8S.

[0110] (3) Roughening treatment: The raw foil passes through the roughening treatment tank to promote the growth of copper nodules on the surface of the electrolytic raw foil, increase the contact area on the side of the pressed insulation layer, and improve the bonding force with the insulation layer; increase the roughness on the non-pressed side to improve the laser absorption capacity. Therefore, in this step, both sides of the copper foil are roughened at the same time, and the process parameters are as follows:

[0111] Copper concentration: 12 g / L;

[0112] Sulfuric acid concentration: 140g / L;

[0113] Temperature: 28℃;

[0114] Plating time: 7S;

[0115] Current density: 60A / dm 2 .

[0116] (4) Curing electroplating: The roughened raw foil is cured to make the roughened copper nodules more firmly bonded to the raw foil substrate. In this step, both sides of the copper foil are cured at the same time. The process parameters are as follows:

[0117] Copper concentration: 50g / L;

[0118] Sulfuric acid concentration: 120g / L;

[0119] Temperature: 50℃;

[0120] Plating time: 7S;

[0121] Current density: 70A / dm 2 .

[0122] (5) Repeat steps (3) and (4) once or twice according to the roughness requirements to increase the number and size of copper nodules after treatment.

[0123] (6) Blackening treatment: A layer of Ni is deposited on both sides of the roughly cured foil to provide better chemical corrosion resistance for the copper foil on the laminated insulation layer and improve the laser absorption ability on the non-laminated surface. The process parameters are as follows:

[0124] K 4 P 2 O 7 =85g / L;

[0125] NiSO 4 .6H 2 O = 4.5 g / L;

[0126] Current density: 10A / dm 2 ;

[0127] Blackening liquid temperature: 40℃;

[0128] Blackening liquid pH = 8.5;

[0129] Electroplating time: 7S.

[0130] (7) Ashing treatment: The foil that has been blackened in stage F is electroplated with a potassium pyrophosphate and zinc sulfate complex solution system. A layer of Zn is electroplated on both sides of the copper foil to provide high-temperature antioxidant properties. The process parameters are as follows:

[0131] K 4 P 2 O 7 =85g / L;

[0132] ZnSO 4 .6H 2 O = 5.5 g / L;

[0133] Current density: 10A / dm 2 ;

[0134] Ashing liquid temperature: 40℃;

[0135] Ashing liquid pH = 8.5;

[0136] Electroplating time: 7S.

[0137] (8) Passivation treatment: When the original foil passes through the chromic anhydride solution system, a layer of Cr is electroplated on both sides of the copper foil to provide room temperature anti-oxidation performance. The process parameters are as follows:

[0138] Cr 6+ (chromic anhydride) = 1.5 g / L;

[0139] Current density: 15A / dm 2 ;

[0140] Passivation solution temperature: 35°C;

[0141] Passivation solution pH = 11;

[0142] Electroplating time: 7S.

[0143] (9) Silane coating: A layer of silane coupling agent is applied on the side of the copper foil laminated insulation layer by roller coating and spraying to enhance the chemical bonding between the copper foil and the substrate. The process parameters are as follows:

[0144] The types of silanes are: epoxy silanes;

[0145] Si content>1200ppm;

[0146] The silane solution is clear and transparent.

[0147] (10) Drying: Drying the residual moisture on the foil surface and promoting the coupling reaction between the silane coupling agent and the hydroxyl groups on the surface of the copper foil to obtain an ultra-thin copper foil for laser processing.

[0148] The basic physical properties of the finished ultra-thin copper foil for laser processing are tested. The thickness of the copper foil is 7μm; the tensile strength of the copper foil is greater than 500MPa. The side of the copper foil laminated insulation layer has a roughening treatment, an anti-rust layer and silane, with a roughness of Rz1.9μm. The non-laminated side of the copper foil has a roughening treatment and an anti-rust layer, with a roughness of Rz0.8μm. The copper teeth height on the non-laminated side of the copper foil is 450nm. The non-laminated side surface is composed of Ni, Zn, Cr, Co and other metals. The non-laminated side surface of the copper foil contains a metal layer, with a total of 60mg / m2 。

Claims

1. An ultra-thin copper foil for laser processing, characterized in that: The pressed insulating layer side and the non-pressed side of the copper foil are roughened, and a metal alloy layer is electroplated on the pressed insulating layer side and silane is coated, and a metal alloy layer is electroplated on the non-pressed side.

2. The ultra-thin copper foil for laser processing according to claim 1, characterized in that: The copper foil has a thickness between 5 μm and 8 μm.

3. The ultra-thin copper foil for laser processing according to claim 1, characterized in that: The thickness of the copper teeth on both sides of the copper foil from trough to trough is greater than 4.5 μm.

4. The ultra-thin copper foil for laser processing according to claim 1, characterized in that: The roughness Rz of the side of the laminated insulating layer is less than 2.5 μm; the roughness Rz of the non-laminated side is between 0.5 μm and 2.0 μm.

5. The ultra-thin copper foil for laser processing according to claim 1, characterized in that: The metal alloy layer is a component of the copper foil anti-rust layer.

6. The ultra-thin copper foil for laser processing according to claim 1 or 5, characterized in that: The metal alloy in the metal alloy layer includes one or more of Ni, Mo, Zn, Cr, Co, and W.

7. The ultra-thin copper foil for laser processing according to claim 1 or 5, characterized in that: The thickness of the metal alloy layer is within 1nm-300nm.

8. The ultra-thin copper foil for laser processing according to claim 1, characterized in that: The copper teeth height of the non-pressed side surface is between 300nm and 800nm.

9. The ultra-thin copper foil for laser processing according to claim 1, characterized in that: The brightness L* value of the non-pressed side is less than 50.

10. A method for preparing an ultra-thin copper foil for laser processing, comprising the following steps: (1) preparing raw foil; (2) passing the raw foil obtained in step (1) through a pickling tank to remove the oxide layer on the surface, and then roughening and curing the pressed insulating layer side and / or the non-pressed side of the raw foil; (3) After the treatment in step (2), the surface of the raw foil is further electroplated with non-copper metal to form an alloy layer; silane is coated on the side of the laminated insulating layer and dried to obtain an ultra-thin copper foil for laser processing.

Citation Information

Patent Citations

  • Manufacturing method of printed wiring board and copper foil for laser processing

    CN104160792B